Q&A with Graham Bendell, Director of Operations, Smart Card Society of Southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Smart card technology could allow ACP countries to leapfrog stages of financial sector development because it eliminates the need for costly and comprehensive infrastructure. Graham Bendell, Director of Operations at the Smart Card Society of Southern Afr